Gestión del talento humano y satisfacción laboral de los trabajadores de la central Parking system Peru, Lima, 2023 - Macedo Inuma, Valeria (2024)
The research conducted at Central Parking System Peru, Lima, 2023, aimed to determine the relationship between human talent management and employee job satisfaction. Using a quantitative approach and a non-experimental design, correlational descriptive data were collected. The results revealed that, based on the dimensions analyzed, the overall perception of the staff regarding the variable was at an intermediate level. Regarding job satisfaction, 63.3% of the respondents considered it at a medium level. The Pearson correlation between both variables was significant, recording a value of 0.999. The specific hypotheses were confirmed by demonstrating significant correlations between employee selection and job satisfaction, compensation and job satisfaction, personal growth and job satisfaction, respectively. The Pearson correlation values were 0.934, 0.817, 0.965, and 0.899, all indicating positive and significant associations. These results suggest that practices are closely linked to employee job satisfaction in the studied organization.